DEVELOPING SONG AS MEDIA IN WRITING DESCRIPTIVE TEXT FOR GRADE X STUDENTS AT SMA N 2 KISARAN - Anisyah and Rafika Dewi Nasution (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2016)
This research is aimed to develop song as media in writing descriptive text basedon the students’ needs and curriculum 2006 for the tenth grade students of SMA N2 Kisaran. There is one problem formulated in this research, How is song mediadeveloped in writing descriptive text to the tenth grade students of SMA N 2Kisaran. In order to answer the problem, the researcher conducted Research andDevelopment (R & D) method. The subject of this research was 2016/2017students of the tenth grade of SMA N 2 Kisaran. The number of the students was35 students. The data of this study was collected by using need analysisquestionnaire and expert judgment. Need analysis questionnaire was calculated byusing percentage to get the information of students’ need before developing songmedia. Expert judgment data were calculated by using score average of criteriainterval of expert judgment to know the validity of song media which has beendeveloped. After the data analyzed, it was found that the experts’ judgment resultwas 3.65 which had a good criteria interval.